Current management and clinical outcomes for patients with haemorrhagic shock due to pelvic fracture in Korean regional trauma centres: A multi-institutional trial. Issue 2 (February 2022) - Jang, Ji Young; Bae, Keum Seok; Chang, Sung Wook; Jung, Kyoungwon; Kim, Dong Hun; Kang, Byung Hee
Highlights: Sixty-six patients (42%) underwent pelvic angiography; 89 (56.7%), preperitoneal pelvic packing; and 27 (17.2%), REBOA. Pelvic external fixation and internal iliac artery ligation were performed in 20 (12.7%), and 13 patients (8.3%), respectively. Since the establishment of regional trauma centers, the clinical outcomes in unstable patients with pelvic fracture significantly improved. Pelvic external fixation has been used less frequently, while pelvic binder and REBOA were significantly more frequently used. Abstract: Introduction: The purpose of this study was to evaluate the current management and clinical outcomes in patients with hemodynamic instability due to pelvic fracture in three regional trauma centres in Korea. Patients and Methods: Three regional trauma centres participated in this study, and 157 patients who were admitted between January 2015 and December 2018 were enroled. Clinical data were collected prospectively as part of the Korean trauma data bank and were analysed retrospectively. Results: The mean age was 59.3 years, and 107 of 157 (68.2%) were male patients. The most common cause of injury was auto-pedestrian accidents, followed by falls and motor vehicle crashes. The mean admission systolic blood pressure and serum lactate level were 86.7 mmHg and 6.68 mmol/L, respectively. Twenty-four patients (15.3%) had a cardiac arrest in the emergency department (ED). The mean injury severity score was 39.1, and the mean probability of survival (Trauma and Injury Severity Score) was 48.7%. Sixty-six patients (42%) underwent pelvic angiography; 89 (56.7%), preperitoneal pelvic packing (PPP); 27 (17.2%), resuscitative endovascular balloon occlusion of the aorta (REBOA); 20 (12.7%), pelvic external fixation (PEF); and 13 patients (8.3%), internal iliac artery ligation (IIAL). Seventy-three patients (46.5%) died, including 40 (25.5%) who died from acute haemorrhage. With each year, the rates of REBOA and pelvic binder use continued to increase ( p <0.001 and p  = 0.005, respectively), but the number of PEF cases significantly decreased ( p  = 0.006). Age, initial lactate, low revised trauma score (RTS), combined abdominal injury, REBOA, and 4-hour requirement of packed red blood cells were independent risk factors associated with mortality, whereas during the period of 2017 and 2018, there were protective factors. The risk factors of mortality due to haemorrhage were cardiac arrest in the ED, RTS, combined chest and abdominal injuries, and IIAL. Conclusions: Since the establishment of regional trauma centres, the clinical outcomes of patients with hemodynamic instability due to pelvic fracture have significantly improved. As a haemostatic procedure for these patients, PEF has been used less frequently, while pelvic binder and REBOA showed significant increase in their use.